Comparison of Waqf Accounting Regulations and Practices: Systematic Literature Review of International Perspectives - Wali Saputra (Universitas Serambi Mekkah, 2025)
This research endeavors to critically examine and juxtapose the regulatory frameworks and accounting methodologies pertaining to waqf across various nations employing the Systematic Literature Review (SLR) methodology. This investigation underscores the significance of transparency and accountability in waqf management, an area that continues to grapple with obstacles stemming from the absence of cohesive international waqf accounting standards. Utilizing the PRISMA framework, 37 scholarly articles published between the years 2010 and 2025 were systematically evaluated from esteemed academic repositories such as Scopus, Web of Science, and ScienceDirect. The findings reveal pronounced divergences among nations regarding their legal infrastructures, institutional arrangements, and the extent of implementation of waqf financial reporting practices. Nations such as Indonesia and Malaysia have demonstrated advancements through the establishment of national standards like PSAK 112 and quality-centric sharia management protocols (MS 1900), whereas other countries such as Nigeria and Sudan continue to encounter institutional impediments and deficiencies in human resources. This study advocates for the formulation of international waqf accounting standards, the enhancement of nazhir capacities, and the digitalization of reporting frameworks to promote more accountable and sustainable governance of waqf on a global scale.